ARCHETYPAL READING IN KATY PERRY’S SELECTED TEENAGE DREAM ALBUM SONGS - Neilandra Ermilla Afriasti; Adeline Grace Marianne Litaay (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study aims to analyze the form of archetypes in the lyrics of the album song “Teenage Dream” by Katy Perry. In this research, the writer analyzes archetypes reflected in the album lyrics of Teenage Dream. In this research, the writer uses the descriptive qualitative method. The data taken are the archetypes used in the album Teenage Dream. The data source is taken from sources on the website in the form of lyrics of the song Last Friday Night (TGIF), Firework, Teenage Dream, California Gurls, Peacock, Circle The Drain, The One That Got Away, and Who Am I Living For?. It can be concluded that in Katy Perry’s songs there are several forms of archetypes that can be categorized. The meaning of archetypes is found in the song Teenage Dream by Katy Perry. Most of Katy Perry’s songs represent what really happens in life. Katy Perry uses figurative language and subconsciously in every song lyrics contain archetypes to express a feeling and wants to tell about the teenager’s life in this album. There are many archetypes reflected in every song’s lyrics, such as persona, anima/animus, self, shadow, the innocent youth, the caregiver, the jester, the ruler, the lover, and the magician